Development of a Semiconductor Time Relay for Locomotives - Serdiuk, V. N; Ochkasov, O. B (Science and Transport Progress, 2022)
Purpose. The need to replace the outdated element base of locomotive electrical apparatuses is urgent under conditions of locomotive overhaul to extend their service life. The main aim of the work is to reduce costs for the operation and repair of rolling stock by increasing the reliability of electrical apparatuses, the introduction of unified technical solutions. Methodology. Using the system-historical approach, the advantages and disadvantages of the main design principles of electrical apparatuses of locomotives are found out. The improvement directions of the elemental base of the time relay have been determined. The need to develop unified technical solutions for the implementation of locomotive time relays is substantiated. Using the methods of applied theory of digital machines and circuit engineering, a semiconductor time relay for locomotives was developed, which provides the possibility of implementing 23 options for time delay without changing the relay design. The proposed methodology allows designing universal electronic relays with any ranges of time delays. A combination of binary counters and a multiplexer is used as the main elements of the time delay control. The absence of elements of control capacitance and active resistance (RC circuits) in the scheme of the proposed semiconductor time relay allows ensuring the stability of the time relay characteristics over the entire operating interval, reducing the maintenance and repair costs of electrical apparatuses. Findings. A unified time relay with a wide range of time delay and the possibility of connecting electrical circuits of locomotives with a supply voltage of 50 and 110 V has been developed. The obtained results make it possible to predict the further development of semiconductor time relays and to apply the developed semiconductor (electronic) time relay for all types of railway rolling stock. Originality. In the work, the development of technologies and the element base of locomotive electrical apparatuses were analysed. The need to improve the element base of electrical apparatuses is substantiated using a time relay example. Practical value. Based on the proposed technical solutions, it is possible to produce a universal semiconductor time relay for locomotives.